Isolation and Identification of Biosurfactant Producing Bacteria from Anaerobic Pond Mud WWTP Palm Oil Industry - Lovi Yona; M. Hasbi M. Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract This study aims to isolate and identify the types of biosurfactant producing bacteria in anaerobic ponds WWTP palm oil industry PT. Sawit Asahan Indah. This research was conducted from April to May 2019. Bacteria were isolated and identified biochemically and 16S R DNA method. The number of bacteria obtained is 8,3 x 106 CFU / ml. The results of the study identified three types of bacteria, namely Proteus vulgaris, Proteus mirabilis and Enterobacter aerogenes. The Proteus vulgaris emulsification index is 25%, the Proteus mirabilis emulsification index is 43.3% and the emulsification index Enterobacter aerogenes is 41.6%. This shows that all three bacteria have the potential to produce biosurfactants. Keywords : Biosurfactant, Proteus vulgaris, Proteus mirabilis, Enterobacter aerogenes, Emulsification Index